PENINGKATAN DAYA SAING UMKM MELALUI INOVASI DESAIN LABEL PRODUK DI DESA PEMATANG TENGAH - Nur Addnin Lubis; Laylan Syafina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
Increasingly intense market competition requires MSMEs to not only present quality products, but also establish a strong visual identity that can attract consumer attention. One important element in introducing a product to the wider public is the creation of informative and attractive product labels. Unfortunately, there are still many MSMEs that have not optimally utilized product labels as a branding and marketing tool. This community service activity was carried out with the aim of increasing the competitiveness of MSMEs in Pematang Tengah Village, Langkat Regency, through the development of product label designs. The methods used include observation, interviews, and making product labels. The study used primary data obtained from interviews with MSME actors. The results of the activity show an increase in the understanding and skills of MSME actors in creating label designs, as well as the realization of products with a more professional appearance. The label innovation helps strengthen product image, expand marketing reach, and grow consumer trust in MSMEs.